Ischemic heart injury leads to HIF1-dependent differential splicing of CaMK2γ - Allison Lesher Williams (Nature Portfolio, 2021)
Abstract Ischemic heart disease is a leading cause of heart failure and hypoxia inducible factor 1 (HIF1) is a key transcription factor in the response to hypoxic injury. Our lab has developed a mouse model in which a mutated, oxygen-stable form of HIF1α (HIF-PPN) can be inducibly expressed in cardiomyocytes. We observed rapid cardiac dilation and loss of contractility in these mice due to lower expression of excitation–contraction coupling genes and reduced calcium flux. As alternative splicing plays an underappreciated role in transcriptional regulation, we used RNA sequencing to search for splicing changes in calcium-handling genes of HIF-PPN hearts and compared them to previous sequencing data from a model of myocardial infarction (MI) to select for transcripts that are modified in a pathological setting. We found overlap between genes differentially expressed in HIF-PPN and post-MI mice (54/131 genes upregulated in HIF-PPN hearts at 1 day and/or 3 days post-MI, and 45/78 downregulated), as well as changes in alternative splicing. Interestingly, calcium/calmodulin dependent protein kinase II, gamma (CAMK2G) was alternatively spliced in both settings, with variant 1 (v1) substantially decreased compared to variants 2 (v2) and 3 (v3). These findings were also replicated in vitro when cells were transfected with HIF-PPN or exposed to hypoxia. Further analysis of CAMK2γ protein abundance revealed only v1 was detectable and substantially decreased up to 7 days post-MI. Rbfox1, a splicing factor of CAMK2G, was also decreased in HIF-PPN and post-MI hearts. Subcellular fractionation showed CAMK2γ v1 was found in the nuclear and cytoplasmic fractions, and abundance decreased in both fractions post-MI. Chromatin immunoprecipitation analysis of HIF1 in post-MI hearts also demonstrated direct HIF1 binding to CAMK2G. CaMK2 is a key transducer of calcium signals in both physiological and pathological settings. The predominantly expressed isoform in the heart, CaMK2δ, has been extensively studied in cardiac injury, but the specific role of CaMK2γ is not well defined. Our data suggest that loss of CaMK2γ after MI is HIF1-dependent and may play an important role in the heart’s calcium signaling and transcriptional response to hypoxia.